Using of Sensitivity Analysis in Road Transport Pricing - Ježek, Jindřich; Nožička, Jiří; Török, Árpád (My University, 2018)
The paper deals with the issue of sensitivity analysis and its possible use in price formation in passenger road transport. The input variables are selected on the model example. Based on the calculation, the sensitivity of the output to these input variables is determined, and the question how these inputs affect the overall result is answered.
Využití citlivostní analýzy v rámci cenotvorby v silniční dopravě
Keywords: sensitivity analysis; transportation; costs; pricing; citlivostní analýza; doprava; náklady; cenotvorba